1998
DOI: 10.1097/00007632-199810010-00011
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological Conditions and Self-Report of Low Back Pain

Abstract: Weather conditions may influence subjective reporting of low back pain significantly. Although the effects are small in magnitude, they should be considered in clinical treatment of the patient with chronic, nonspecific low back pain. Pain scores may demonstrate greater interaction with certain weather conditions in individuals perceiving sensitivity to those conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 13 publications
3
30
0
1
Order By: Relevance
“…From an epidemiological viewpoint, an association has been established between cold exposure and musculoskeletal symptoms and complaints, especially for the neck and upper arms (14)(15)(16)(17). A high prevalence of muscle problems in the neck and low back was detected in the study: 21% in each area.…”
Section: Discussionmentioning
confidence: 85%
“…From an epidemiological viewpoint, an association has been established between cold exposure and musculoskeletal symptoms and complaints, especially for the neck and upper arms (14)(15)(16)(17). A high prevalence of muscle problems in the neck and low back was detected in the study: 21% in each area.…”
Section: Discussionmentioning
confidence: 85%
“…14 15 McGorry et al found a relationship between low back pain and temperature. 16 Positive correlations have been found between relative humidity and pain in osteoarthritis (OA) and RA, humidity and stiffness in RA and cloudiness, humidity and pain in RA. 9 10 15 17 Gorin et al found positive associations between pain in RA and cold, overcast days and also following days with high barometric pressure.…”
mentioning
confidence: 99%
“…A review of the literature revealed that general symptoms of diseases such as rheumatoid arthritis, osteoarthritis and [3][4][5][6][7][8][9]. Some studies carried out more specific analyses and found that different weather conditions caused a change only in rheumatoid arthritis [10][11][12], only in fibromyalgia [8,12] or only in back pain [3,14] cases.…”
Section: Discussionmentioning
confidence: 99%